Judicial Response to Crime Against Women in India - Bhardwaj, Dr . Manish (Innovative Research Thoughts, 2018)
Violence against women has long been an issue, in both peaceful and conflicted environments. In addition to rape and murder, this violence may be found at home, at work, in jails, and on the streets. Less is known, prosecuted, and punished for crimes against women than are really committed. If there aren't any specific research on occurrence, it's impossible to come up with ideas for reducing or eliminating such violence. More research on the psychology of the perpetrators of this violence is urgently required. It is imperative that violent incidents be properly examined and preventative measures created. The accused should face swift and harsh punishment, which would also serve as a deterrence. A civilised society must reexamine its claims to civility if it cannot guarantee the safety of half its citizens.